PENERAPAN PERATURAN DAN SANKSI ADMINISTRASI PERPAJAKAN TERHADAP KEPATUHAN FORMAL WAJIB PAJAK BESAR DI KANTOR PELAYANAN PAJAK MADYA SEMARANG - Anwar, Subhan Nur Mulla Ali (Jurnal Suara Keadilan, 2023)
Tax sanctions are regulations made by state agencies that regulate taxation issues to cerate legal guarantees and at the same time as a form of control over all taxpayers to comply with tax regulations. Administrative sanctions are created and implemented with the aim of complying and complying with taxpayers in reporting taxes that must be imposed to the state. Administrative sanctions applied can be in the form of fines or increased taxes charged to taxpayers. Giving dependents on tax obligations who are known to have not carried out their obligations is considered to have a deterrent effect and is also considered to be able to regulate discipline and accuracy for the obligator so that in the future he is better able to carry out his obligations and also report his taxes. With the application of administrative sanctions there is an increase in state revenue through the tax sector.Understanding of taxes and the seriousness of taxpayers to report and pay their tax obligations can reflect the level of awareness of taxpayers. The high or low level of taxpayers in complying with their tax obligations is influenced by several factors, one of which is taxpayer awareness. Understanding of taxes and the seriousness of taxpayers to report and pay their tax obligations can reflect the level of awareness of taxpayers, increasing public knowledge about educational taxation will have a positive impact on taxpayer awareness to pay their tax obligations.